A BIM approach for construction safety: applications, barriers and solutions. Issue 9 (19th October 2018) - Marefat, Akbar; Toosi, Hossein; Mahmoudi Hasankhanlo, Reza
Abstract : Purpose: Construction industry bears a lot of casualties and accidents more than other high-risk industries annually. Thus, the use of new technologies such, as building information modeling, automatic rule checking, information technology-based safety systems in order to implement the rules and safety standards, better controls the performance of workers on site and make high coordination between operational executives, leading to create a secure environment in projects by reducing accidents. The paper aims to discuss these issues. Design/methodology/approach: In this study, a researcher-designed questionnaire was distributed among 200 companies that are active in the field of construction to evaluate the effect of building information model (BIM) for safety projects and barriers to adoption. Only 70 percent of questionnaires were returned. Statistical Package for the Social Sciences analysis has been used to determine the correlation coefficient among the respondents. Findings: The results show the factors that lead to failure in the adoption of BIM in Iran are lack of well-trained personnel, proper social infrastructure, guidance and governmental supports. Originality/value: Finally, the authors presented solutions for overcoming barriers and proposed some factors leading to the successful adoption of BIM in Iran.